Antioxidant Materials in Oral and Maxillofacial Tissue Regeneration: A Narrative Review of the Literature - Niloufar Abedi; Zahra Sadat Sajadi-Javan; Monireh Kouhi; Legha Ansari; Abbasali Khademi; Seeram Ramakrishna (MDPI AG, 2023)
Oral and maxillofacial tissue defects caused by trauma, tumor reactions, congenital anomalies, ischemic diseases, infectious diseases, surgical resection, and odontogenic cysts present a formidable challenge for reconstruction. Tissue regeneration using functional biomaterials and cell therapy strategies has raised great concerns in the treatment of damaged tissue during the past few decades. However, during biomaterials implantation and cell transplantation, the production of excessive reactive oxygen species (ROS) may hinder tissue repair as it commonly causes severe tissue injuries leading to the cell damage. These products exist in form of oxidant molecules such as hydrogen peroxide, superoxide ions, hydroxyl radicals, and nitrogen oxide. These days, many scientists have focused on the application of ROS-scavenging components in the body during the tissue regeneration process. One of these scavenging components is antioxidants, which are beneficial materials for the treatment of damaged tissues and keeping tissues safe against free radicals. Antioxidants are divided into natural and synthetic sources. In the current review article, different antioxidant sources and their mechanism of action are discussed. The applications of antioxidants in the regeneration of oral and maxillofacial tissues, including hard tissues of cranial, alveolar bone, dental tissue, oral soft tissue (dental pulp, periodontal soft tissue), facial nerve, and cartilage tissues, are also highlighted in the following parts.